Development of an advanced nano-satellite VELOX-I – study of column-level ADC architectures for high speed CMOS image sensors - Liu, Lifen. (2013)
This Final Year Project (FYP) is to design a 10-bit Column-Parallel Analog-to-Digital Convertor (ADC) using CMOS technology. This ADC design is used as a part of High Speed CMOS Image Sensors, and this design must be satisfy the requirements of size and speed.